Om Sverige i polsk press 1989-1999 - Żmuda-Trzebiatowska, Magdalena (Folia Scandinavica Posnaniensia, 2007)
An analysis o f articles about Sweden which have appeared in the Polish press from 1989 to 1999 makes it possible to distinguish the most frequent subjects chosen by Polish journalists. These subjects include the unsolved case of the assassination of Olof Palme, the drawbacks of the Swedish welfare state, the controversies connected with Swedish neutrality, the discussions on how far equality can go and the problems of a multicultural country; as well as Swedish peculiarities such as alcohol policy, liberal morals, the position of the Church in a secularized society and the attachment to the monarchy. This article covers several examples o f these most popular topics. It also examines the way in which they have been presented, with regard to the traditional perception of Sweden by Poles as well as to the sense of Polish national identity noticeable in the journalists’ comments. The problems connected with these issues are discussed in greater detail in the author’s doctoral thesis in the chapter which deals with the perception of Sweden in Poland.